APPRAISAL, COMPETENCIES AND PERFORMANCE MANAGEMENT OF STAFF AT AN ACUTE TRUST IN THE NATIONAL HEALTH SERVICE OF GREAT BRITAIN - Datta, Helen (2007)
Appraisals can be defined as a process undertaken by oneself or others to analyse and assess the range of professional knowledge, skills and attitudes, which directly and indirectly affect the performance of nursing care activities.